The mystery of human participation in the Paschal Mystery of Christ according to medieval mysticism of the low countries - Dorota Lekka (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The article analyses the question of human participation in the paschal mystery of Christ in the understanding of medieval mystics of the Low Countries. The presentation consist of three parts. The first part explains the concept of the mystery of human participation in the paschal mystery of Christ, the second presents the foundations of human participation in the mystery of Christ on the basis of selected writings by John of Ruusbroec, Beatrice of Nazaret, Hadewijch, as well as Arnhem Mystical Sermons and The Evangelical Pearl. The last part explains the ways of human participation as conceived of in the above-mentioned medieval mystical works.